Emancypacja jako nowy nurt rehabilitacji - Konarska, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article contains reflections on the essence of emancipation, conditions and opportunities for its realization to people with disabilities. The topic of discussion is undertaken formation by parents, teachers and other persons involved in the rehabilitation process of such personality traits that facilitate self-realization and auto- nomy. The ability to achieve self-realization is a form of emancipation. Taken at the end of the discussion about the legitimacy of multiplication terms.